2012
DOI: 10.1111/j.1472-4642.2011.00877.x
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of warming up a hotspot: species range shifts within a centre of bee diversity

Abstract: Aim  Bees are the most important pollinators of flowering plants and essential ecological keystone species contributing to the integrity of most terrestrial ecosystems. Here, we examine the potential impact of climate change on bees’ geographic range in a global biodiversity hotspot. Location  South Africa with a focus on the Cape Floristic Region (CFR) diversity hotspot. Methods  Geographic ranges of 12 South African bee species representing dominant distribution types were studied, and the climate change imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 60 publications
2
39
0
1
Order By: Relevance
“…As climatic factors clearly have an influence on bee distribution, climate change can be expected to affect many bee species by causing spatial and/or temporal mismatch between plants and pollinators, and impact them through extreme weather events and shifts in distributional ranges (Memmott et al 2007;Goulson et al 2015). Roberts et al (2011) demonstrated that three generalists and three specialist species of Colletes might be threatened by climate change, and for the global bee diversity hotspot of the GCFR, substantial range contraction for most bee species under a scenario of warming climate is predicted (Kuhlmann et al 2012). In our study, the significant association of a number of climatic variables (precipitation of the wettest month, irradiance of the warmest quarter and growing degree days) with species richness estimates corroborates the results of the earlier studies and suggests that changing climate might have a direct effect on bee diversity at the global to regional scales (Williams et al 2009;Pradervand et al 2014;Scriven et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As climatic factors clearly have an influence on bee distribution, climate change can be expected to affect many bee species by causing spatial and/or temporal mismatch between plants and pollinators, and impact them through extreme weather events and shifts in distributional ranges (Memmott et al 2007;Goulson et al 2015). Roberts et al (2011) demonstrated that three generalists and three specialist species of Colletes might be threatened by climate change, and for the global bee diversity hotspot of the GCFR, substantial range contraction for most bee species under a scenario of warming climate is predicted (Kuhlmann et al 2012). In our study, the significant association of a number of climatic variables (precipitation of the wettest month, irradiance of the warmest quarter and growing degree days) with species richness estimates corroborates the results of the earlier studies and suggests that changing climate might have a direct effect on bee diversity at the global to regional scales (Williams et al 2009;Pradervand et al 2014;Scriven et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple drivers of wild bee decline can act on various spatial scales ranging from local land-use change and unsustainable agricultural practices (Quintero et al 2009;Brittain and Potts 2011;Rollin et al 2015) to regional biological invasions of pathogens (Cameron et al 2011) and non-native species (Ghazoul 2004), and continental-scale climate change (Hegland et al 2009). While local factors of bee decline are relatively well known and potential mitigation strategies at a landscape scale have been outlined (Zurbuchen and Müller 2012), regional and continental-scale threats to bee diversity have only been marginally explored (Roberts et al 2011;Kuhlmann et al 2012). This paucity of large-scale studies reflects a shortage of comprehensive, taxonomically reliable distribution data for most geographic regions.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, bumblebee populations seem to be more sensitive to other threats when they reach their climatic limits (Williams & Osborne, 2009). Further, there is some indication that future climate change could have severe impacts on wild bee faunas (Kuhlmann et al, 2012) including bumblebees (Kirilenko & Hanley, 2007;Herrera et al, 2014).…”
Section: Toward a New Pollinator Communitymentioning
confidence: 99%
“…Parmesan & Yohe, 2003;Chen et al, 2011) including bees (e.g. Kuhlmann et al, 2012). On the other hand, the gradual changes can lead to modification of species' phenology (Polgar et al, 2013;Kharouba et al, 2014; for wild bees see Bartomeus et al, 2011).…”
Section: Effects Of Climate Changementioning
confidence: 99%
“…Should there be any climate change (for example, less rainfall) resulting in a higher water table depth, it could result in a reduction of species richness, as some species might not survive with the changed conditions. Accounting for South Africa's semi-arid environment, urbanization, groundwater extraction and the creation of more bore holes will ultimately cause a change in hydrology and therefore impact the Restionaceae species niche [21,22].…”
Section: Hydrological Niche Modellingmentioning
confidence: 99%